Cardiovascular Z‐scores in fetuses with tetralogy of Fallot. (9th November 2014) - Wu, L.‐H.; Wang, N.; Xie, H.‐N.; Du, L.; Peng, R.
ABSTRACT Objective To establish formulae for the calculation of fetal cardiovascular Z‐scores based on femur length (FL), and to compare cardiovascular parameters between fetuses with tetralogy of Fallot (TOF) and normal fetuses in order to assess their value for the prenatal diagnosis of TOF. Methods A total of 329 normal fetuses and 43 fetuses with TOF were included in this study. Eleven cardiovascular dimensions were measured offline after cardiac spatiotemporal image correlation volume acquisition. Normal cardiovascular Z‐score formulae were constructed for these measurements based on FL by performing a standard regression analysis followed by weighted regression of absolute residual values. The following ratios were calculated: right ventricular internal diameter (RVID) to left ventricular internal diameter (LVID) and pulmonary artery diameter (PA) to aorta diameter (Ao). Subsequently, all parameters were compared between the normal and TOF groups. Results Formulae for calculating Z‐scores for the 11 cardiovascular dimensions were constructed. FL was significantly correlated with all cardiovascular dimensions assessed (r = 0.816–0.944, P < 0.001 for all). RVID, Ao, PA, aortic arch isthmus, and ductus arteriosus mean Z‐scores and PA/Ao ratio were statistically significantly different between normal fetuses and those with TOF. In the TOF group, all Ao Z‐scores (43/43) were > + 2 and all PA/Ao ratios (43/43) were below the normal 95% range. However, only 48.8% (21/43) of the PA Z‐scores were < −2. Conclusions The cardiovascular Z‐score formulae developed can provide a quantitative basis for the prenatal diagnosis of TOF. Aortic dilatation and abnormal PA/Ao ratio may be markers for the antenatal diagnosis of TOF. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.